Endovascular Treatment of Middle Cerebral Artery M2 Occlusion Strokes: Clinical and Procedural Predictors of Outcomes. Issue 5 (November 2017) - Mokin, Maxim; Primiani, Christopher T; Ren, Zeguang; Kan, Peter; Duckworth, Edward; Turner, Raymond D; Turk, Aquilla S; Fargen, Kyle M; Dabus, Guilherme; Linfante, Italo; Dumont, Travis M; Brasiliense, Leonardo B C; et al.
Abstract : BACKGROUND: : Patients with strokes from M2 segment middle cerebral artery (MCA) occlusion have been underrepresented in recent randomized trials of endovascular therapy. OBJECTIVE: : To better understand the clinical, imaging, and procedural predictors of successful recanalization and clinical outcomes in this population of patients. METHODS: : We performed a multicenter retrospective analysis of consecutive patients with acute MCA M2 segment occlusion who underwent thrombectomy with stent retrievers or primary aspiration thrombectomy (including A Direct Aspiration First Pass Technique approach). We correlated clinical and radiographic outcomes with demographic, clinical, and technical characteristics. RESULTS: : One hundred and seventeen patients were included in analysis (median admission National Institutes of Health stroke scale [NIHSS] score 15, mean age 67.0 ± 14.5, 42% females). Good clinical outcome at 3 months (modified Rankin scale [mRS] ≤ 2) was achieved in 56% of patients. Treatment beyond 6 h of symptoms onset ( P = .69, OR 0.80, 95% CI 0.38‐1.73) and age over 80 ( P = .47, OR 0.65, 95% CI 0.25‐1.70) were not predictive of poor outcome. NIHSS > 15 was a strong predictor of clinical outcome, based on mRS distribution at 3 months ( P = .0085, OR 0.35, 95% CI 0.16‐0.74). Direct aspiration and primary stent retriever thrombectomy approaches showed similar radiographic and clinical success rates. CONCLUSION: : Advanced age and time to treatment beyond 6 h from symptom onset were not predictive of clinical outcome with thrombectomy. NIHSS score above 15 was a strong predictor of outcome. Direct aspiration and primary stent retriever thrombectomy showed similar efficacy.